DESIGNING MULTIMEDIA FOR LECTURERSâ NEED IN TEACHING ENGLISH PRONUNCIATION - Sri, Damayanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2014)
The objectives of this research are to find out the studentsâ error in pronunciang some selected English words and to design multimedia based on the studentsâ need in teaching pronunciation. The researcher took 8 students as sample randomly of 300 students at English Education Study program ofÂ  Cokroaminoto Palopo University. This research tries to develop of some theoriesÂ  in Phonology and create or design the media (multimedia) in teaching pronunciation. The result of this research shows the studentsâ error in pronouncing vowel, diphthong, and Consonant when they find the word which is not familiar with them and when they find the word which consists of sound that is not exist in Indonesian sound. So, the design of media in teaching English Pronunciation is multimedia which consists of some materials in vowel, consonant, and diphthong. This media also provides sounds in pronouncing some English words.